Analisis Hukum Terhadap Pertimbangan Hakim Atas Vonis Nihil Kepada Pelaku Tindak Pidana Korupsi - Fitria Ramadhani Siregar; Nanang Tomi Sitorus (Jurnal Ilmiah Penegakan Hukum, 2022)
This study aims to determine and analyze the verdict of zero in the corruption case committed by the defendant on behalf of Heru Hidayat which was reported in the corruption case at PT. Asuransi Jiwasraya which cost the state Rp. 16 trillion and the defendant was sentenced to life imprisonment, but for the Corruption Crime Case at PT. ASABRI caused a loss to the state of Rp. 22.78 trillion, but the defendant and the judge handed down a zero sentence verdict, of course this greatly disturbed the justice of the people in Indonesia. This research method uses a type of normative juridical research, namely research conducted by means of a literature study and a case approach. After the data is collected, a qualitative analysis is carried out. The results of this study are to explain that a zero sentence is regulated in Article 67 of the Criminal Code which states that if someone has been sentenced to death or life imprisonment, then no other punishment may be imposed except for the revocation of certain rights. However, these provisions limit the possibility of people who commit various criminal acts who are then tried either at the same time or tried separately for a total of more than 20 years in prison. Based on Article 272 of the Criminal Procedure Code, the convict is sentenced to imprisonment or confinement and then sentenced to a similar sentence before serving the sentence previously imposed, then the sentence is carried out successively starting with the sentence that was imposed first